2017
DOI: 10.3892/or.2017.6098
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of microRNA-1274a induces cell apoptosis through regulation of BMPR1B in clear cell renal cell carcinoma

Abstract: Our previous studies of the microRNA (miRNA) expression signature in clear cell renal cell carcinoma (ccRCC) indicated that miRNA-1274a (miR-1274a) was significantly upregulated in clinical specimens, suggesting that miR-1274a may act as an oncogenic miRNA in ccRCC. The aim of this study was to investigate the functional roles of miR-1274a and identify downstream tumor-suppressive targets regulated by miR‑1274a in ccRCC cells. Functional studies of miR-1274a were carried out by anti-miRNA to investigate cell p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 23 publications
(35 reference statements)
1
16
0
Order By: Relevance
“…As the most common type of adult kidney cancer, ccRCC is characterized by poor prognosis and a high risk of metastasis and recurrence (29). Epigenetic modifications, including RNA modification (21,22,24), DNA methylation (30), histone modification (31) and microRNA changes (32,33), serve diverse functions in the malignant progression and prognosis of ccRCC. As the most prevalent type of internal RNA modification, m6A RNA methylation has gained increasing attention over the past decade (5,7,8,12).…”
Section: Discussionmentioning
confidence: 99%
“…As the most common type of adult kidney cancer, ccRCC is characterized by poor prognosis and a high risk of metastasis and recurrence (29). Epigenetic modifications, including RNA modification (21,22,24), DNA methylation (30), histone modification (31) and microRNA changes (32,33), serve diverse functions in the malignant progression and prognosis of ccRCC. As the most prevalent type of internal RNA modification, m6A RNA methylation has gained increasing attention over the past decade (5,7,8,12).…”
Section: Discussionmentioning
confidence: 99%
“…An increasing number of previous studies have demonstrated that miRNAs are dysregulated in approximately all types of human malignancy, including ccRCC (13)(14)(15). miRNA (miR)-19a (16), miR-224 (17), miR-1274a (18) and miR-543 (19) were upregulated in ccRCC, whereas, miR-30a (20), miR-200a (21), miR-384 (22) and miR-411 (23) were downregulated. These aberrantly expressed miRNAs are implicated in the oncogenesis and progression of ccRCC, and regulate various crucial biological processes, including cell proliferation, apoptosis, metastasis and angiogenesis (13,24).…”
Section: Introductionmentioning
confidence: 99%
“…There is no study in the literature investigating the role of miR-1260a, and miR-1260b miRNA molecules in ovarian cancer. The expression level of miR-1260a was investigated in breast, kidney, gastric cancer, malignant melanoma, hepatocellular carcinoma, colorectal carcinoma, and esophageal squamous cell carcinoma, and was detected to have been upregulated in these cancers [23][24][25][26][27][28][29][30]. In addition, miR-1260a expression level was reported to have high level expression in the serum, and FFPE tissues of prostate cancer patients compared with the BPH controls, and higher expression was also reported in prostate cell strains [31,32,62].…”
Section: Discussionmentioning
confidence: 99%
“…miRNAs were shown to cause functional changes in cancer cells, and therefore had roles in various cancers [21]. miR-1260a was shown to be located on 14q24.3 chromosome region, and this miRNA was upregulated in breast cancer, malignant melanoma, hepatocellular carcinoma, colorectal carcinoma, esophageal squamous cell carcinoma, kidney carcinoma, and gastric cancer [22][23][24][25][26][27][28][29]. Although there was no study in the literature suggesting that miR-1260a was speci cally associated with ovarian cancer, miR-1260a was suggested to have possibly been upregulated in ovarian cancer in the assumption after the results of the study investigating that in prostate cancer patients [28] [30].…”
Section: Introductionmentioning
confidence: 99%